Domino Mufrodat Card Media to Improve Arabic Vocabulary - Sofia, Sofia; Ulum, Fatkhul; Hasmawati, Hasmawati (Phonologie : Journal of Language and Literature, 2024)
Abstract. This research aims to determine the planning, process and results of increasing mastery of Arabic vocabulary in the learning process using mufrodat domino cards. This type of research is classroom action research. The subjects of this research were IVB students at SDIT Al-Khwarizmi East Kalimantan with a total of 31 students. The data collection techniques used in this research were tests and observations. This research was carried out in 2 cycles and each cycle consisted of 2 meetings. The results of this research show that the average score obtained in cycle I reached 74% and in cycle II the average score of students reached 90%. These results indicate that students' mastery of Arabic vocabulary has increased by using mufrodat domino cards.Keyword: Improvement, Vocabulary Mastery, Mufrodat Domino Cards